UJI AKTIVITAS MINYAK ATSIRI DAUN SALAM (SYZYGIUM POLYANTHUM WALP) TERHADAP RAYAP TANAH (COPTOTERMES CURVIGNATHUS HOLMGREN) - li, Er; Wardenaar, Evy; hati, Mufli (Universitas Tanjungpura, 2015)
The study aimsto evaluated the activity of salam leaf (Syzygium polyanthum Walp) against subterranean termite (Coptotermes curvignathus Holmgren) and found the best level to inhibit the termite attack. Salam leaf was cut into small pieces, macerated with methanol for 24 hours, and evaporated with rotary evaporator. The essential oils were put into whatman paper with dosage level 0 ml; 0.1 ml;0.2 ml; 0.3 ml; 0.4 ml respectively. Then the paper put into medium of bioassay to termites for 3 days. The result of showet that dosage level 0.4 ml made 100% termites mortality with paper weight loss 0.42%. The higher dosage level resulted the higher mortality of termites. The optimal level of essential oils to inhibited the subterranean termites Coptotermes curvignathus Holmgren attack was achieved on level 0.3 ml. Keywords: Antitermites activity,Coptotermes curvignathus Holmgren, Essential oils, Syzygium polyanthum Walp.